Integration of Educational and Conservative Landscapes: Designing a Biology Department Garden for Local Biodiversity Conservation - Yulia, Fransiska Poppy (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to design a Local Biodiversity Conservation Garden in the Biology Department, evaluate changes in community appreciation after the garden redesign, compare the richness of local and exotic plant species, and identify plant species with the largest canopy cover to support ecological and aesthetic functions. Methodology: Field observation, vegetation inventory, questionnaire survey, canopy cover analysis, species classification based on regional distribution references, manual garden design sketching and scanning, descriptive quantitative analysis. Tools used included measuring tape, lux meter, plant identification references, questionnaire forms, digital scanner, statistical analysis software, and biodiversity documentation records. Main Findings: The redesigned conservation garden significantly improved aesthetic appreciation among Biology Department community members. Plant species richness increased substantially, with local species dominating over exotic species. Community perception shifted positively toward the reorganized garden. Vegetation stratification showed clear ecological structuring, while canopy analysis identified dominant species contributing most to shade formation and microclimate regulation within the conservation area. Novelty/Originality of this study: This study introduces an integrated campus garden design model that combines biodiversity conservation, ecological restoration, and landscape aesthetics using predominantly local plant species. It advances existing knowledge by demonstrating how academic green spaces can function simultaneously as conservation areas, educational laboratories, and ecological infrastructure supporting biodiversity enhancement within higher education institutions.